2019
DOI: 10.1103/physrevd.99.114508
|View full text |Cite
|
Sign up to set email alerts
|

Quark mass dependence of on-shell and half off-shell scattering amplitudes from Bethe-Salpeter wave function inside the interaction range

Abstract: We evaluate scattering amplitudes at on-shell and half off-shell for I = 2 S-wave two-pion system using the Bethe-Salpeter wave function inside the interaction range in the quenched QCD. The scattering length and effective range are extracted from these scattering amplitudes. Quark mass dependence of them is investigated with the pion mass ranged in 0.52-0.86 GeV. We examine consistency between a result by the conventional finite volume method and our estimate, as well as the phenomenological value.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(70 reference statements)
2
4
0
Order By: Relevance
“…It is found that the results of δ (k) obtained from the two methods, the finite volume method and the extended relation, completely agree with each other, and the half-off-shell amplitude can be calculated in a wide range of the momentum with reasonable statistical error. Furthermore, we confirm that similar results for the on-shell and half-off-shell amplitudes are obtained in smaller m π [6].…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…It is found that the results of δ (k) obtained from the two methods, the finite volume method and the extended relation, completely agree with each other, and the half-off-shell amplitude can be calculated in a wide range of the momentum with reasonable statistical error. Furthermore, we confirm that similar results for the on-shell and half-off-shell amplitudes are obtained in smaller m π [6].…”
Section: Introductionsupporting
confidence: 89%
“…In this report, we discuss conditions for this t independence through a definition of the scattering amplitude on the lattice under some assumptions. The results in this report have already been presented in our paper [6].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…While alternatives, including the potential method (Refs. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]), the mapping onto harmonic oscillators (Ref. [28]) and the imposition of spherical walls (Refs.…”
Section: Introductionmentioning
confidence: 99%